2016
DOI: 10.3727/096368916x691501
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of Multiple Biological Therapies for Ischemic Cardiac Disease

Abstract: The development of cell-and gene-based strategies for regenerative medicine offers a therapeutic option for the repair and potential regeneration of damaged cardiac tissue post-myocardial infarction (MI). Human umbilical cord subepithelial cell-derived stem cells (hUC-SECs), human bone marrow-derived mesenchymal stem cells (hBM-MSCs), and human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs), all derived from human tissue, have been shown to have in vitro and in vivo therapeutic potential. Add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 69 publications
0
10
0
1
Order By: Relevance
“…Paracrine MSC properties are important in response to injury in tissue regeneration 7174 . The hUC-MSC is an attractive candidate for regenerative therapy because of its remarkable paracrine action 22,26 . HGF is involved in the mechanism that induces angiogenesis and inhibits fibrosis, and important to tissue repair 5458 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paracrine MSC properties are important in response to injury in tissue regeneration 7174 . The hUC-MSC is an attractive candidate for regenerative therapy because of its remarkable paracrine action 22,26 . HGF is involved in the mechanism that induces angiogenesis and inhibits fibrosis, and important to tissue repair 5458 .…”
Section: Discussionmentioning
confidence: 99%
“…Human umbilical cord-derived MSCs (hUC-MSCs) used in this study represent a promising allogeneic cell source for stem cell therapy among diverse MSC types, with increasing clinical evidence 2225 . hUC-MSCs exhibit low HLA expression and higher paracrine effects compared to human bone marrow stem cells (hBM-MSC) 22,26,27 . Furthermore, intravenously infused allogenic hUC-MSC treatments induced no adverse host immune responses and produced clinically significant improvements in patients either with heart failure, with spinal cord, or with multiple sclerosis 2225 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in addition to the preserved differentiation and immunomodulation capacity compared with BM-MSCs, iPS-MSCs have been demonstrated to be superior with higher accessibility, less oncogenicity, and greater expandability to overcome the inherent limitations in BM-MSCs for clinical application [11][12][13]. Preclinical studies have shown great success in applying iPS-MSCs for treating renal ischemia/reperfusion injury [14], ischemic cardiac disease [15], chronic obstructive pulmonary disease [16], and osteoarthritis [17]. We recently showed that iPS-MSCs conferred renoprotection in adriamycin nephrosis [18], supporting the potential of iPS-MSCs in treating kidney diseases.…”
Section: Introductionmentioning
confidence: 99%
“…(Imai et al, 2016;Kang et al, 2016;Lukasiewicz, 2016;von Segesser et al, 2016). Stem cell transplantation is a candidate therapy that has recently been tested to treat ischemia-related diseases, such as stroke (Kasahara et al, 2016;Vahidy et al, 2016;Wang et al, 2016), heart infarction (Henry et al, 2016;Li et al, 2016;Winters et al, 2016), and hindlimb ischemia (Kishimoto et al, 2016;Shin et al, 2016;Yoshida et al, 2016). There are two kinds of stem cells mainly used in transplantation studies; these include mesenchymal stem cells (MSCs) and endothelial progenitor cells (EPCs).…”
Section: Introductionmentioning
confidence: 99%